Pengaruh Cita Rasa, Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian: Survei pada Beli Kopi Surakarta - Tiariesta Khansa Tsabita; Sumaryanto Sumaryanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of taste, price, and service quality on purchasing decisions for buy coffee products in Surakarta. This research is a survey of buy coffee consumers in Surakarta. This study used a sample of 100 people with this sampling technique using accidental sampling technique, which means that the sampling method is accidental (accidental) by taking cases or respondents who happen to be there or available somewhere in accordance with the research context. Data collection techniques using literature studies. The data analysis technique uses multiple linear regression analysis methods, t test, f test, and determination test. The results showed that taste affects the decision to buy coffee products, price affects the decision to buy coffee products, and service quality affects the decision to buy coffee products.